Linking cyber strategy with grand strategy: the case of the United States. Issue 2 (4th May 2018) - Weber, Valentin
ABSTRACT: The aim of this article is to study whether U.S. cyber strategy is integrated into U.S. grand strategy. In consideration of cyber strategy documents, three case studies and elite interviews find that a link between the two strategic layers is largely missing. Even though U.S. cyber strategy documents contain higher political goals, they do not meet other criteria that indicate links to a grand strategy. Those are a unified list of geopolitical challenges, a balance of ends and means, the integration of military, economic and political means, and the provision of a strategic narrative. Thereby, the documents leave the articulation of grand strategy at the initial stages and do not develop it further. The lack of grand strategy in cyberspace is also visible in U.S. tactical behaviour. The three chosen case studies show that the various U.S. military, economic and political actions taking place under the Obama administration were isolated from each other. Hence, they failed to create a combined impact greater than the sum of their separate effects. This study fills the demonstrated gap in U.S. strategy and concludes by presenting a cyber strategy that is integrated into U.S. grand strategy.